THE STRUGGLE OF EROS AGAINST THANATOS IN THE NOVEL "LADY CHATTERLEY`S LOVER" BY D.H.LAWRENCE - Ejupi, Vlera; Siljanovska, Liljana; Iseni, Arburim (European Scientific Journal, ESJ, 2014)
The more time passes by, we get more and more aware of the everyday`s tiresome fight between the good and the evil. This gets even worse,when we become victims with a lot of consequences as a result of thisextremely dangerous accompanies of everything that we do in our everydaylife. Sigmund Freud, brilliantly gives names to these inevitable happeningsof our lives,Thanatos and Eros.There is a deep chasm between the two ofthese, but still, the way people who get a proper education, are always taughtthat it is Eros, the good side of our lives which is the final winner. It is DavidHerbert Lawrence that developed a real revolution throughout his writing toshow this horrible struggle, through the reflection of sequences of hisbiography in his novels. Also this struggle is very much present in the `LadyChatterley`s Lover`, where the characters are victims of throughout strugglethroughout the whole book.